Methodology of teaching physical culture (Journal of Universal Science Research, 2023)
Physical culture is historically realized, first of all, in the process of preparing the younger generation and adults for creative work, under the influence of the practical requirements of society. At the same time, in the formation of a system of teaching and educating physical culture in society, as a key factor in the formation of various motor skills and abilities and the expansion of human activity opportunities, physical abilities, as well as intellectual, moral and aesthetic education helps to increase.